Answer:
The correct answer is (5 - 7)^2
Step-by-step explanation:
To find this, start with the outermost equation g(x).
g(x) = x^2
Now put the next equation (h(x)) in for x in this equation.
(G ▪ H)(x) = (x - 7)^2
Now, put the number in for x in the equation given.
(G ▪ H)(x) = (5 - 7)^2
Answer:
when x=6, y=30
when x=7.5, y=37.5
Step-by-step explanation:
Just plug in the value of x into the equation y=5x
so when x=6, the equation will be y=5(6). In this case y=30
when x =7.5, the equation will be y=5(7.5). So y=37.5
Answer:
a scalar between 0 and 1
Step-by-step explanation:
i just took the test on EdG. :)
Answer: 12
Step-by-step explanation:
6y - 3z
6(4) - 3(4)
24 - 12
12